The Effectiveness of What’s The Number Method in Students Reading Ability - Siti Yuliana; Ika Rakhmawati (STKIP PGRI Trenggalek, 2021)
This research discusses the effectiveness of what’s the number method in students’ reading ability. The objective of this research is to know “what’s the number” method in students reading ability. The statement of the research problem is Do students achieve better reading ability after being taught using what’s the number method? This research uses quantitative research. The researcher uses a pre-experimental design for research design. The data collecting method are pretest, treatment, and posttest. The subject of the research is students of the fourth semester of the English department at Bhinneka PGRI University. It is conducted in students’ fourth-semester class A with the sample is 15 students. This is using cluster sampling. The researcher gives students a pretest, after that they are given treatment then the researcher gives a posttest for the students. The result is students’ score have increased after the treatment. The mean of the posttest is higher than the pretest which is 7.27 > 4.33, and the significance is 0.000 < 0.05. It can be concluded that “What’s the number method” is significantly effective for students reading ability. Therefore, it can answer the statement of the research problem. In conclusion that “What’s the number method” is significantly effective for students reading ability at the fourth semester English department of Bhinneka PGRI University. So, what’s the number method was an effective method to improve students reading ability and this method can be applied in the classroom.